THE IMPORTANCE OF URATE PATHWAY ENZYMES ACTIVITY AND ITS RELATION WITH OXIDATIVE STRESS IN PROGRESSION AND INVASION OF HUMAN COLORECTAL CANCER: Urate pathway in colon cancer - Veljkovic, Andrej; Hadzi-Djokic, Jovan; Stanojevic, Goran; Brankovic, Branko; Skakic, Aleksandar; Damjanovic, Ivana; Stojanovic, Mladen; Smelcerovic, Andrija; Kocic, Gordana (Acta medicae Medianae, 2021)
Background and objectives: Colorectal cancer (CRC) is one of the most often diagnosed cancers and the main reason for mortality connected with tumor diseases. There is still a shortage of examination including the influence of urate pathway enzymes in progressiveness and invasion of CRC, so the present study investigated the role of Adenosine deaminase (ADA), 5′-nucleotidase (5′-NT) and Xanthine oxidase (XO) activity, concerning TBA-reactive substances (TBARS) as a marker of oxidative stress in progression and invasion of human colorectal cancer. Materials and Methods: We took cancer tissue specimens, and also a healthy control tissue and tissue surrounding the tumor from 50 patients with primary colorectal cancers in all four TNM clinical stages of the disease. We made 10% homogenates in which we conducted the study with proper methods. Results: The activity of ADA and XO in tumor tissue and tissue adjacent to the tumor was significantly higher when compared to healthy colon tissue. The 5′-NT is not significantly higher in carcinoma tissue. The highest activity of ADA and XO is in T2 and T3 tumor stadiums. TBARS has the highest concentration in T3 and T4 stadiums of the tumor. Conclusions: Presented results suggest that one of the possible causes of oxidative stress in colon carcinoma could be high XO and ADA activity. It may include those enzymes in the malignant transformation of the colon epithelium, as well as in the progression and invasion of human colon cancer. In this way, the estimation of ADA and XO activity could help in assessing the margins to establish the extensiveness of colon resection. They can have significance in diagnosis, but in the prognosis of the disease also.
Keywords: 1; colorectal cancer 2; Adenosine deaminase 3; 5′-nucleotidase 4; Xanthine oxidase 5; oxidative stress